Maternal and Neonatal Outcome in Pregnant Women with Obesity in a Single Tertiary Referral Hospital in January - December 2017 - Virdayanti, Dian Puspita; Gumilar, Khanisyah Erza (UNUSA Press, 2020)
Background: Maternal obesity is defined when BMI is above 30. It is now considered one of the most commonly occurring risk factors seen in obstetric practice and it increased risks of specific complications, and to medical, surgical and technical challenges in providing safe maternity care. Objectives: This study aims to review maternal dan neonatal outcomes and complications from pregnant women with obesity in Soetomo General Hospital on January - December 2017. Methods: Retrospective cross-sectional study by using medical record data of Dr. Soetomo General Hospital on January - December 2017. Results: There were 297 (21,5%) of maternal obesity from 1384 deliveries, in which the majority age range from 20-34 years old and multiparity. The most BMI category was BMI class 1 (61%). Caesarean section (77,4%) in this study became a major proportion in mode of delivery. In our study, the incidence of hypertension in pregnancy was high (45,4%), while the incidence of severe preeclampsia were 20,9%. The incidence of gestational diabetes were 7,1%, and pregestational diabetes were 3,4%. In our cases, there were 294 cases (94,2%) of livebirth, while there were four stillbirth cases. The incidence of intrauterine fetal death were four cases. There were 11 cases of macrosomia, 7 in 11 came from mother with obesity class III. Other neonatal complications are intrauterine growth restriction which were 26 cases and 18 cases congenital malformation. Conclusion: Most maternal complications in obese pregnant women are severe preeclampsia with mode of delivery by cesarean section. Gestational diabetes cases were found mostly in maternal obesity class I, while pregestational diabetes cases were found mostly in maternal obesity class II. Most neonatal Apgar score in our study were between 7-10, while most of congenital malformation was omphalocele